2020
DOI: 10.3390/atmos11020124
|View full text |Cite
|
Sign up to set email alerts
|

Australian Lidar Measurements of Aerosol Layers Associated with the 2015 Calbuco Eruption

Abstract: The Calbuco volcano in southern Chile (41.3° S, 72.6° W) underwent three separate eruptions on 22–23 April 2015. Following the eruptions, distinct layers of enhanced lidar backscatter at 532 nm were observed in the lower stratosphere above Buckland Park, South Australia (34.6° S, 138.5° E), and Kingston, Tasmania (43.0° S, 147.3° E), during a small set of observations in April–May 2015. Using atmospheric trajectory modelling and measurements from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…(2015a) and Klekociuk et al. (2020). We initially attempted to calibrate the AAD lidar following the method of O'Connor et al.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…(2015a) and Klekociuk et al. (2020). We initially attempted to calibrate the AAD lidar following the method of O'Connor et al.…”
Section: Methodsmentioning
confidence: 96%
“…In addition to the laser ceilometers, the AAD deployed a 532 nm depolarization lidar that provides range-resolved vertical profiles of backscatter and depolarization ratio. The lidar operated at 30 m vertical resolution, with further specifications given in Huang et al (2015a) and Klekociuk et al (2020). We initially attempted to calibrate the AAD lidar following the method of O'Connor et al (2004), which relies on periods of fully attenuating, non-precipitating cloud.…”
Section: Depolarization Lidar (Used For Particle Phase Determination)mentioning
confidence: 99%
“…Limited set of cloud radiation and aerosol properties south of 60°S and circumpolar quantification of aerosol properties Kuma et al (2020), Klekociuk et al (2020a), Hartery et al (2020), Schmale et al (2019) BL and free troposphere structure, together with vertical distributions of liquid and mixedphase clouds and aerosols properties, over cold SO waters where SLW and mixed-phase BL clouds are frequent.…”
mentioning
confidence: 99%
“…Recently Klekociuk et al 12 reported a case of stratospheric aerosols modulated by the gravity wave. A displacement of stratospheric aerosols over a distance of 600 m was observed produced by passing gravity waves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Baines and Sacks 13 modelled the generation of stratospheric gravity waves by volcano eruptions but not consider their effects on aerosols. Klekociuk et al 12 reported the displacement of stratospheric aerosols by passing gravity waves of atmospheric origin. In general, the volcanic gravity waves have been extensively studied but mostly on their effects on seismic activities and upper atmospheric air 3 13 while their effects on aerosols is little explored.…”
Section: Introductionmentioning
confidence: 99%